Globalization and the least developed countries [ potentials and pitfalls - Bigman, David (CABI, 2007)
This book evaluates the policies of least developed countries (LDCs) and the decisions that they now face against the backdrop of the changes in the structure of the global economy and in the globalization process itself. It analyses possible scenarios nd alternative trade and growth policies that are likely to affect the LDCs and their poor population, in order to draw lessons for future policies. The book has 6 chapters and a subject index.